New Faces of the Folk Church - Plank, Katarina; Egnell, Helene; Lundgren, Linnea (Karlstad University, 2024)
The project is based on ethnographic fieldwork: netnographic mapping of homepages, observations and interviews with people that are participating in activities arranged by churches and parishes.

The material that is analysed comprises of fieldnotes, interviews, observations with people that are doing bodily practices in church settings. We have also photo documented religious material culture and activities taking place. Other printed material has also been collected in the field: pamphlets, information sheets and artefacts.

The research projects also uses archive studies, document studies and netnographic studies. The archive and document studies collect data on issues that have been handled by the cathedral chapter (the juridicial body of the diocese).

Projektet baseras på etnografiskt fältarbete; efter en inledande netnografisk kartläggningsstudie av hemsidor har vi arbetat med observationer och intervjuer med människor som deltar i verksamheter arrangerade av kyrkliga församlingar.

Det material som analyseras inom projektet består av fältanteckningar, intervjuer, samtal och observationer med religiösa människor och med människor som befinner sig i religiösa miljöer för att utöva någon form av kroppslig praktik. Projektet har även genererat fotomaterial som dokumenterar religiös materiell kultur och aktiviteter som äger rum. Även material som finns tillgängligt i fält har insamlats, så som pamfletter, informationsmaterial och artefakter.

Forskningsprojektet använder sig även av arkivstudier, dokumentstudier och netnografiska kartläggningsstudier. Arkiv- och dokumentstudierna samlar in data om ärenden som hanterats av Domkapitlet i Stockholms stift, eller som behandlats av kyrkoråd och kyrkofullmäktigeförsamlingar.
Folkkyrkans nya ansikten
Keywords: Administrative units; Administrativa enheter; Buildings; Byggnader; Utility and governmental services; Allmännyttiga och offentliga tjänster; pedagogy of religion; religionspedagogik; interfaith dialogue; religionsdialog; religious practice; religionsutövning; geography of religion; religionsgeografi; religion and religions; religion och religioner; theology; teologi; ethnography of religion; religionsetnografi; anthropology of religion; religionsantropologi; sociology of religion; religionssociologi; phenomenology of religion; religionsfenomenologi; science of religion; religionsvetenskap; Life-long/continuing education; Livslångt lärande/vidareutbildning; General health and well-being; Allmän hälsa och välbefinnande; Cultural activities and participation; Kulturaktiviteter och deltagande; Religion and values; Religion och värderingar; Social change; Social förändring; Religious Studies; Religionsvetenskap; History of Religions; Religionshistoria; Other Humanities not elsewhere specified; Övrig annan humaniora; Society; Samhälle och kultur